First-Place Loving and Last-Place Loathing: How Rank in the Distribution of Performance Affects Effort Provision - Gill, David; Kissová, Zdenka; Lee, Jaesun; Prowse, Victoria (Management Science, 2019)
Rank-order relative-performance evaluation, in which pay, promotion, symbolic awards, and educational achievement depend on the rank of individuals in the distribution of performance, is ubiquitous. Whenever organizations use rank-order relative-performance evaluation, people receive feedback about their rank. Using a real-effort experiment, we aim to discover whether people respond to the specific rank that they achieve. In particular, we leverage random variation in the allocation of rank among subjects who exerted the same effort to obtain a causal estimate of the rank response function that describes how effort provision responds to the content of rank-order feedback. We find that the rank response function is U-shaped. Subjects exhibit “first-place loving” and “last-place loathing”: that is, subjects work hardest after being ranked first or last. We discuss implications of our findings for the optimal design of performance feedback policies, workplace organizational structures, and incentives schemes. Data and the supplementary web appendix are available at https://doi.org/10.1287/mnsc.2017.2907 . This paper was accepted by Uri Gneezy, behavioral economics.